2017
DOI: 10.1002/jbm.a.36007
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale physicochemical properties of chain‐ and step‐growth polymerized PEG hydrogels affect cell‐material interactions

Abstract: Poly(ethylene glycol) (PEG) hydrogels provide a versatile platform to develop cell instructive materials through incorporation of a variety of cell adhesive ligands and degradable chemistries. Synthesis of PEG gels can be accomplished via two mechanisms: chain and step growth polymerizations. The mechanism dramatically impacts hydrogel nanostructure, whereby chain polymerized hydrogels are highly heterogeneous and step growth networks exhibit more uniform structures. Underpinning these alterations in nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…This level is much greater than expected based on loosely-associated siRNA/NPs considering the surface area to volume ratios of the gels. In addition to surface-assocated siRNA/NPs, chain-polymerized hydrogels, which are employed here, contain significant network heterogeneities, which underpins variable mesh sizes [47]. Thus, it is likely that some embedded siRNA/NP have lower diffusional hindrance, contributing to this apparent deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This level is much greater than expected based on loosely-associated siRNA/NPs considering the surface area to volume ratios of the gels. In addition to surface-assocated siRNA/NPs, chain-polymerized hydrogels, which are employed here, contain significant network heterogeneities, which underpins variable mesh sizes [47]. Thus, it is likely that some embedded siRNA/NP have lower diffusional hindrance, contributing to this apparent deviation.…”
Section: Discussionmentioning
confidence: 99%
“…This likelihood is further supported by sustained siRNA/NP release observed from some degradable gels despite overall gel mesh sizes exceeding siRNA/NP size. Greater consistency between mesh size and release may be afforded by use of alternative crosslinking chemistries including click-based thiol-ene polymerizations which form networks with greater homogeneity [47].…”
Section: Discussionmentioning
confidence: 99%
“…[57] These results agree with recent studies which showed that chain versus step-growth polymerizations impact cellular morphology and function. [58,59] The influence of the LM content on cell morphology was also studied. Gels with different concentrations of LM 521 (100 and 500 µg mL -1 ) were prepared and compared with gels without LM521 after 7 days in culture.…”
Section: D Hybrid Laminin Hydrogels With Controlled Degradability and Mechanical Propertiesmentioning
confidence: 99%
“…In addition, thiol–ene PEG hydrogels exhibit high cytocompatibility, precise spatiotemporal control of gelation, tunable degradation, and versatile modulation of biophysical and biochemical properties. The versatility of these hydrogels is demonstrated through extensive applications, ranging from protein and drug delivery, cartilage development, osteogenic differentiation, endothelial tubulogenesis, brain tumor models, synthetic matrix mimics, 2D culture substrates, and islet and cell encapsulation . However, these applications have been exclusively conducted in vitro, yielding little insight into the in vivo behavior of these hydrogels.…”
mentioning
confidence: 99%